1996
DOI: 10.1002/pen.10389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data on the kinetics of isothermal polymer crystallization

Abstract: The kinetic crystallization model of Avrami is generally accepted as a starting point for the analysis of isothermal polymer crystallization. However, in most cases, the experimental situation is complicated by a n incubation time prior to isothermal crystallization, so that the Avrami equation must be modified. Moreover, the experimental data are often limited in number and restricted to a n intermediate crystallinity range. Furthermore, data of isothermal crystallization experiments performed at different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…melt-crystallization with respect to the temperature-mark at about l 70°C. 6 Moreover, the results for k(Tin) and x(Tin) are in qualitative agreement with data reported elsewhere for isothermal and non-isothermal melt-crystallization of PET. 12 • 13 It is concluded that the kinetics of polymer crystallizations, being characterized by a single A vrami index n, can be described in the vicinity of the inflexion point as well with a nucleation and crystal-growth model as, formally, with an apparent m-order reaction model.…”
Section: Aka(t) =K (T)(__!i_)supporting
confidence: 90%
See 3 more Smart Citations
“…melt-crystallization with respect to the temperature-mark at about l 70°C. 6 Moreover, the results for k(Tin) and x(Tin) are in qualitative agreement with data reported elsewhere for isothermal and non-isothermal melt-crystallization of PET. 12 • 13 It is concluded that the kinetics of polymer crystallizations, being characterized by a single A vrami index n, can be described in the vicinity of the inflexion point as well with a nucleation and crystal-growth model as, formally, with an apparent m-order reaction model.…”
Section: Aka(t) =K (T)(__!i_)supporting
confidence: 90%
“…Thus, a( Tin) has been found to be approximately independent of the temperature, the temperature-dependent rate constant and the heating (or cooling) rate q. a(Tin) is only dependent on the apparent reaction-order m. Because m is approximately independent of q, if an inflexion point exists, eq 5 is valid for a wide range of q-values, although not for q = 0. 6 On the other side, the isothermal crystallization model of A vrami, being based on the nucleation and growth characteristics of crystalline phases, also shows an inflexion point for n > 1 as well as for the formal cases with n < 0. The three-parameter Avrami equation function, 7 • 8 being the result of the isothermal nucleation and growth theory, is given by…”
Section: Aka(t) =K (T)(__!i_)mentioning
confidence: 99%
See 2 more Smart Citations
“…The three-parameter Avrami equation functions @(t) show a n inflection point for n > 1. The time-values of the inflection points ti, and the values of O(t,,) have been calculated by the author in a previous work (8). They are given by…”
mentioning
confidence: 99%